PENEGAKAN HUKUM LINGKUNGAN TERHADAP AZAS MUTLAK “STRICT LIABILITY” DALAM PENGELOLAAN LINGKUNGAN HIDUP - edy Sunarno Sunarno (VERITAS, 2018)
Basically the law in Indonesia has provided arrangements that allow theapplication of this strict liability concept, however, it can not be denied because ofthe various reasons already mentioned above, in practice the application of strictliability is not easy. The principle of absolute liability (strict liability) is theprinciple of legal liability (liability) that has developed long ago that started froma case in England that is Rylands v. Fletcher in 1868. In this case the Court ofAppeals in the United Kingdom established a defining criterion that an activity oruse of resources may be subject to strict liability if such use is non-natural oroutside the usual, or unusual. Conventional liability has so far adhered to liabilitybased on fault, meaning that no one can be liable if there are no errors in him. Inthe case of the doctrine environment it will create obstacles to the law in courtbecause the doctrine is unable to effectively anticipate the impact of modernindustrial activities that contain potential risks.